Production of inter-specific hybrid:s ofLabeo dyocheilus (McClelland) and Laheo rohita (Hamilton) - KUSHWAHAI, B; SINGH, HARPAL; SINGH, I J; SINGH, AJEET (The Indian Journal of Animal Sciences, 2011)
Production of inter-specific hybrids ofLabeo dyocheilus and Labeo rohita was taken up with the objective of combining traits of cold tolerance of L. dyocheilus and fast growth of L. rohita. Hybridization using dry fertilization with fresh stripped eggs and diluted milt from ovaprim induced female and male of L. dyocheilus and L. rohita gave excellent results. The fertilization ,ranged between 91 and 94% and water hardening of eggs took 2-3 h. The diameter of fully swollen eggs ranged 4.12 to 4.11 rom. The hatching time varied between 14-18 h and hatching rate from 89.68 to 91.34%. Though majority of morphometric trait ratios among parent species and their hybrids showed insignificant difference but traits showing differences were more inclined towards the maternal parent. Â